Early Childhood Physical, Cognitive, Socio-Emotional Development - Arif Rahman Prasetyo (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
There are terms that describe reality in early childhood, including problem age, golden age, and preschool age. The term problem age is based on natural causes because at this time, children become egocentric and stubborn individuals. While the golden age refers to research that the best developmental stage for honing a child's potential is during the first five years. The preschool age is a period where the child's first place of learning is the family environment. Markers of this period end when the child enters elementary school. This research is a library research with the aim of knowing the picture in early childhood about physical, cognitive, and social-emotional development. The results of this study are: 1) Early childhood takes place in the age range 2-6 years, 2) physically, children in the early period have experienced changes in body structure that are more muscular and fatty, and start developing gross and fine skills, 3) cognitively, early childhood enters the pre-operational stage, which is characterized by imaginative thoughts and the use of symbols, 4) socially, children in the early days begin to explore the environment by playing with peers. Whereas emotionally, fear, sadness, anger, jealousy, happiness, pride, love, affection, and curiosity are the dominant emotions in this period.